Analysis of Inventory Turnover and Debt to Equity Ratio in Increasing Profitability in PT. Nusantara IV Plantations, Medan - Seprida Hanum (Journal of International Conference Proceedings (JICP), 2021)
The exploration led by the creator means to break down stock can expand benefit as estimated by Return On Resources (ROA) and to examine obligation to value proportion can build productivity as estimated by Return On Resources (ROA) At PT. Nusantara IV Medan Manor. This sort of exploration is distinct, with the object of examination is the monetary side of PT. Nusantara IV Medan Estate. Where in research in dissecting stock turnover and obligation to value proportion can expand productivity. The outcomes show that the declining stock turnover doesn't muchly affect the organization's benefit, which implies that the organization can deal with its resources well, in order to augment the benefits it procures. The obligation to value proportion which has expanded additionally doesn't muchly affect the degree of organization benefit, which implies that the organization can deal with the organization's obligations in expanding the organization's deals, so it can amplify the benefits it gets. Catchphrases: Stock Turnover, Obligation to value proportion (DER), Return on Resources (ROA)